Development of an antisense oligonucleotide-mediated exon skipping therapeutic strategy for Mucolipidosis II: validation at RNA level - Matos, Liliana (2021)
Lysosomal Storage Disorders (LSDs) are a group of rare inherited metabolic diseases caused by the malfunction of the lysosomal system, which results in the accumulation of undegraded substrates inside the lysosomes and leads to severe and progressive pathology. Despite there is currently a broad understanding of the molecular defects behind LSDs, curative therapies have been approved for only few of these diseases whereas existing treatments are still mostly symptomatic with several limitations. Mucolipidosis type II alpha/beta (ML II) is one of most severe LSDs, which is caused by the total deficiency of the GlcNAc-1-phosphotransferase, a key enzyme for the formation of specific targeting signals on lysosomal hydrolases to lysosomes. GlcNAc-1-phosphotransferase is a multimeric enzyme complex encoded by two genes: GNPTAB and GNPTG. One of the most frequent ML II causal mutation is a dinucleotide deletion on exon 19 of GNPTAB (c.3503_3504del) that leads to the generation of a truncated protein, loss of GlcNAc-1-phosphotransferase activity, and missorting of multiple lysosomal enzymes. Presently, there is no therapy available for ML II. In this study we explored the possibility of an innovative therapeutic strategy for ML II based on the use of antisense oligonucleotides (AOs) capable to induce the skipping of GNPTAB exon 19 harboring the most common disease-causing mutation, c.3503_3504del. The approach confirmed the ability of specific AOs for RNA splicing modulation, thus paving the way for future studies on the therapeutic potential of this strategy.